2022
DOI: 10.1016/j.hpb.2021.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Pain management, fluid therapy and thromboprophylaxis after pancreatoduodenectomy: a worldwide survey among surgeons

Abstract: Background: The aim of this survey was to assess practices regarding pain management, fluid therapy and thromboprophylaxis in patients undergoing pancreatoduodenectomy on a global basis.Methods: This survey study among surgeons from eight (inter)national scientific societies was performed according to the CHERRIES guideline.Results: Overall, 236 surgeons completed the survey. ERAS protocols are used by 61% of surgeons and respectively 82%, 93%, 57% believed there is a relationship between pain management, flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…However, rather than focusing on the exact opioid volumes, we emphasize that the learning health system model of iterative opioid reduction is freely adaptable by other hospitals. Although the global experience of post–pancreatic resection care may be different than our US hospital, the components of our enhanced recovery program, including the purposeful opioid reduction protocols, can benefit patients regardless of international differences in LOS . While numerical pain scores and refill rates following discharge are an acceptable measure of pain control, we did not solicit patient feedback (through surveys) regarding their pain control expectations or postoperative quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…However, rather than focusing on the exact opioid volumes, we emphasize that the learning health system model of iterative opioid reduction is freely adaptable by other hospitals. Although the global experience of post–pancreatic resection care may be different than our US hospital, the components of our enhanced recovery program, including the purposeful opioid reduction protocols, can benefit patients regardless of international differences in LOS . While numerical pain scores and refill rates following discharge are an acceptable measure of pain control, we did not solicit patient feedback (through surveys) regarding their pain control expectations or postoperative quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The reported use of EA varies from 11% to 85%, 1 and a recent international survey showed that only 61% of surgeons regularly follow ERAS protocols. 7 Other acute pain management options include continuous wound infiltration, spinal or intrathecal (IT) blocks, and regional blocks such as transversus abdominis plane (TAP) blocks. In North America, TAP block was ranked as the most commonly used technique for analgesia, but there is a lack of research on the effectiveness of this strategy for PD.…”
Section: Introductionmentioning
confidence: 99%
“…In North America, TAP block was ranked as the most commonly used technique for analgesia, but there is a lack of research on the effectiveness of this strategy for PD. 7 With substantial variability in current clinical practice and the paucity of data, further research is needed to determine the optimal method for pain control after open PD that uses an opioid-sparing approach. The current study aims to evaluate our institutional experience and compare the effectiveness of EA, IT morphine blocks, and regional TAP blocks for open PD.…”
Section: Introductionmentioning
confidence: 99%
“… 2–6 The most used alternative to EA is intravenous (iv) morphine. 1–3 , 7 _ENREF_3 The advantages of iv morphine are that most patients are eligible (eg patients with coagulation disorders or spine anatomy alterations) and that it is a less invasive method compared to EA. The disadvantages of iv morphine are the suboptimal pain control and a higher consumption of opioids compared to EA with associated side effects.…”
Section: Introductionmentioning
confidence: 99%